Category-Specific Visual Recognition and Aging from the PACE Theory Perspective: Evidence for a Presemantic Deficit in Aging Object Recognition. Issue 5 (19th October 2016) - Bordaberry, Pierre; Gerlach, Christian; Lenoble, Quentin
Abstract : Background/Study Context : The objective of this study was to investigate the object recognition deficit in aging. Age-related declines were examined from the presemantic account of category effects (PACE) theory perspective (Gerlach, 2009, Cognition, 111, 281–301). This view assumes that the structural similarity/dissimilarity inherent in living and nonliving objects, respectively, can account for a wide range of category-specific effects. Methods : In two experiments on object recognition, young (36 participants, 18–27 years) and older (36 participants, 53–69 years) adult participants' performances were compared. Results : The young adults' results corroborate the PACE theory expectations. The results of the older adults showed an impairment in recognition of structurally similar objects irrespective of semantic category. Conclusion : The two sets of results suggest that a deficit in the selection stage of the PACE theory (visual long-term memory matching) could be responsible for these impairments. Indeed, the older group showed a deficit when this stage was most relevant. This article emphasize on the critical need for taking into account structural component of the stimuli and type of tasks in further studies.